Gluten-free food product - Karim, Roselina (2014)
The present invention relates to a gluten-free composition for preparation of gluten-free food product. The composition comprises of brewer’s rice and hydroxylpropyl methylcellulose. The present invention also relates to a method for preparing a gluten-free food product comprises of providing a mixture; stirring the mixture to form a dough; resting the dough; extruding the dough to form extrudate; coating the extrudate with alkaline solution; and baking the extrudate to form the gluten-free food product characterized in that, adding brewer’s rice flour and hydroxypropyl methylcellulose to the mixture.